A Study on the Effects of Implementing Base Isolation System for Existing RC Buildings on Soft Soil - Muhammad F. Firmansyah; Ahmad B. Habieba; Faimun Faimun (Institut Teknologi Sepuluh Nopember (ITS), 2025)
The occurrence of earthquakes is frequent in Indonesia due to its position in a highly active tectonic zone. One approach to improve the seismic performance of existing buildings is through the use of base isolation. The concept of using base isolation systems aims to increase the natural period of structures and provide additional damping to reduce seismic forces on the structures. A comparative study was performed between a fixed base system and base isolated system in a 13-story reinforced concrete building located in Surabaya on soft soil. Subsequently, these models were evaluated for their structural response using the nonlinear time history analysis. The results demonstrate that the use of base isolation systems can significantly elongate the building’s natural period, resulting in a significant decrease in the base shear, acceleration response, drift, and the plastic hinge formed. This study proves that this technology is suitable to be applied to existing buildings with satisfactory results.